Recomendações Portuguesas para Utilização de Terapêuticas Biológicas em Crianças e Adolescentes com Artrite Idiopática Juvenil. Atualização de 2016 - Santos, Maria José (2016)
Introduction: To provide evidence-based guidance for the rati onal and safe prescripti on of biological therapies in children and adolescents with juvenile idiopathic arthriti s (JIAs), considering the latest available evidence and the new licensed biologics. Methods: Rheumatologists and Pediatricians with experti se in Pediatric Rheumatology updated the recommendati ons endorsed by the Portuguese Society of Rheumatology and the Portuguese Society of Pediatrics based on published evidence and expert opinion. The level of agreement with fi nal propositi ons was voted using an online survey. Results: In total, 20 recommendati ons to guide the use of biological therapy in children and adolescents with JIAs are issued, comprising 4 general principles and 16 specifi c recommendati ons. A consensus was achieved regarding the eligibility and response criteria, maintenance of biological therapy, and procedures in case of non-response, for each JIA category. Specifi crecommendati ons concerning safety procedures were also updated. Discussion: These recommendati ons take into account the specifi citi es of each JIA category and are intended to conti nuously improve the management of JIA pati ents.